Corporate Social Responsibility sebagai Strategi Nilai Tambah Ekonomi Berbasis Kepatuhan Lingkungan - Indah Dwiprigitningtias (CV. Kalimasada Group, 2025)
This article explores the implementation of Corporate Social Responsibility (CSR) as a strategic approach to generate economic added value through environmental compliance. The study investigates how CSR programs that align with environmental regulations contribute not only to legal adherence but also to long-term economic benefits for companies. The research adopts a mixed-methods approach, combining qualitative analysis of regulatory frameworks and CSR reports with quantitative data from selected manufacturing and industrial sectors. The findings reveal that companies integrating environmental compliance into their CSR initiatives tend to experience higher public trust, improved brand image, and operational efficiency. These advantages indirectly enhance economic value by reducing regulatory risks and fostering consumer loyalty. Furthermore, the study highlights that CSR is no longer merely a philanthropic activity but a strategic investment in sustainability and legal risk mitigation. This research provides insight for policymakers and business leaders on how CSR aligned with environmental law can serve as a dual driver of compliance and competitive advantage in an increasingly eco-conscious economic landscape.